MONTE CARLO SIMULATION OF I-, Br-, AND Cl- IN WATER USING AB INITIO PAIR POTENSIAL FUNCTIONS - Harno Dwi Pranowo (Indonesian Journal of Chemistry, 2007)
Monte Carlo simulations were performed for I-, Br- and Cl-, in water using ab initio pair potential. The systems consisting of one anion in 215 solvent molecules have been simulated at 298 K. Anion-water pair potentials have been newly developed based on ab initio calculations of split valence basis set plus polarization quality. The structure of the solvated ion is discussed in terms of radial distribution functions, coordination number and pair potential distribution. Structural properties were investigated by means of radial distribution functions and their running integration numbers, leading for the first solvation shell to an average 12.60 H2O around I- with I--O distance of 3.74 Å and I--H distance of 2.86 Å, 11.84 H2O around Br- with Br--O distance of 3.40 Å and Br--H distance of 2.42 Å, and 10.68 H2O around Cl- with Cl--O distance of 3.20 Å and Cl--H distance of 2.24 Å, respectively. The structure of the water-anion complexes are agreed with dipole orientation. Pair energy distribution of hydrated anions showed that the pair interaction energy are increase from I-, Cl-, to Br-, namely, -6.28, -9.98 and -13.67 kcal/mol, respectively. The coordination number distribution analysis for the first solvation shell of the all hydrated anions indicated a high exchange rate for the first solvation shell ligands.